Tinjauan Yuridis atas Peredaran Produk Obat Pelangsing Ilegal Melalui Perdagangan Online yang Beresiko terhadap Kesehatan - Warahmah, Sipa Mawadah; Ansari, Teuku Syahrul (CV. Rayyan Dwi Bharata, 2023)
In realizing a healthy state, medicine and food play a very important role. However, not all drugs and foods distributed online have a distribution permit and meet other requirements in accordance with laws and regulations so that they can threaten public health. The circulation of drug products online has the risk of circulating certain drugs that are often misused and illegal products that harm public health, one of which is illegal direct drug products such as Slim Strong, Slim Fast, Slimming Pro, etc.), containing BKO sibutramin which can cause side effects such as palpitations, shortness of breath, anxiety, and hallucinations. The method used in writing this article is a qualitative approach with a descriptive method of analysis. Data collection techniques are carried out by literature study. Data and information are collected from various related literature such as books, journals, related laws and regulations, government documents, news in mass media both print and electronic, and others. Data and information are combined and analyzed based on discussion groups. The last stage, the results of the analysis that has been made, conclusions are drawn as answers to research questions and also some suggestions or recommendations to relevant stakeholders. This study emphasizes that supervision carried out by the Food and Drug Administration on the circulation of illegal slimming drug products as a form of comprehensive supervision ranging from pre-market to post-market supervision. This supervision is strengthened by the existence of Presidential Instruction (Inpres) Number 3 of 2017 concerning Increasing the Effectiveness of Food and Drug Control. Then, law enforcement that can have a deterrent effect is to apply criminal sanctions, as stipulated in Article 197 Jo. Article 106 paragraph (1) of RI Law Number 36 of 2009 concerning Health as amended by Article 60 number 10 of RI Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of RI Law on Job Creation and in RI Law Number 8 of 1999 concerning Consumer Protection.